If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -3 = 6x + 39 Reorder the terms: -3 + 10x = 6x + 39 Reorder the terms: -3 + 10x = 39 + 6x Solving -3 + 10x = 39 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -3 + 10x + -6x = 39 + 6x + -6x Combine like terms: 10x + -6x = 4x -3 + 4x = 39 + 6x + -6x Combine like terms: 6x + -6x = 0 -3 + 4x = 39 + 0 -3 + 4x = 39 Add '3' to each side of the equation. -3 + 3 + 4x = 39 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 39 + 3 4x = 39 + 3 Combine like terms: 39 + 3 = 42 4x = 42 Divide each side by '4'. x = 10.5 Simplifying x = 10.5
| a=-5n+2n | | 2x+1=53 | | 5x+64=180 | | 7(11x-8)=77x-10 | | 13.0x-180forx=50 | | 8g+6=9g-10 | | x+77+x+62+45=180 | | 2(3x-7)=(5x-6) | | 9(x+5)=108 | | (2x+43)=(2x-3) | | X+-16=9 | | 13x-1=8x+39 | | n^2=-n | | 3*2-5+4*3-8+5*2= | | x-4+1=-3-x | | 3+3u=18 | | 250+150x=300y | | 10-3p+4p=20 | | F(4)=-3(-9)+10 | | 200+.25n=325 | | x+3x-2=18 | | 6m-2m= | | 9x+15=8x+4 | | 7=-5+4x | | (2x+50)=(5x+5) | | 56+x+85+42=180 | | 4x-5=102 | | 8-6(m-3)+4=4(m+7) | | 6x-1+11=53 | | x+-20=-16 | | F(3)=4(-5)-7 | | 9t^2-72t-54=0 |